CO2-brine-rock interactions as a result of long term experiment onto rock samples from Chabowo anticline, Poland - Wdowin, Magdalena; Tarkowski, Radosław; Manecki, Maciej (Geology, Geophysics and Environment, 2013)
The presented work concerns investigations of CO2 -brine-rock interactions conducted over a period of 20-months. Experiments were carried out at laboratory scale with the use of equipment specifically designed for this purpose. Research materials (reservoir and cap rocks) were taken from the Chabowo 3 well located within Chabowo anticline. The experiments were carried out at room temperature (about 25ºC) and pressure about 6 MPa. For samples before and after the experiment a numerous investigations were carried out i.e. petrophysical (porosity, surface area, threshold diameter, average capillary, framework and bulk densities) and petrological-mineralogical characteristics. Also brine used for examination before and after experiment was analyzed (chemical analysis). Petrophysical results have shown a significant decrease of porosity (from 17.0% to 7.5%) and surface area (from 0.395 m2 /g to 0.196 m2 /g) in case of sandstone. These changes are caused probably by crystallization of halite in pore spaces, because mineralogical analysis (XRD) has shown the presence of halite (3–5% vol. in the rock) after experiment. More detailed results were obtained during mineralogical analyses of thin sections. These results have shown in sandstone samples a small increase of porosity and a small decrease of feldspar and cements (carbonate and clay) as well as matrix which suggests dissolution of these constituents. For claystone – after experiment XRD clay fraction has shown absence of clay minerals such as montmorillonite, which may also be caused by interaction between the rock, CO2 and brine. Dissolution of some minerals is evidenced by chemical analysis of brine where amounts of most tested ions increase after experiment for both sandstone and claystone.